2015
DOI: 10.1007/s11064-014-1508-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Neuroprotective Potential of Derivatives of the Iron Chelating Drug Deferiprone

Abstract: There is growing evidence for alterations in iron homeostasis during aging that are exacerbated in neurodegenerative diseases such as Alzheimer's disease. However, since essentially all neurodegenerative diseases are multi-factorial in the sense that there are a large number of mechanisms that can be identified as contributing to nerve cell death, iron chelators that have additional activities might be the most useful for the treatment of age-related CNS diseases. We have described a series of cell culture-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Specific chelation targeting strategies are also required for the treatment of diseases associated with the excess accumulation of xenobiotic and essential metals in specific organs e.g., excess iron, copper, zinc and aluminium in the brain, all of which have been implicated in neurodegenerative diseases [1,17]. Such strategies should include the selection of specific chelators that can cross the blood-brain barrier such as deferiprone [18,19]. Substantial improvements have been observed in different categories of patients with neurodegenerative diseases using deferiprone including pantothenate kinase-associated neurodegeneration (PKAN) and Friedreich's Ataxia [12,[20][21][22][23][24].…”
Section: Examples Of the Clinical Applications Of Chelator Metal Compmentioning
confidence: 99%
“…Specific chelation targeting strategies are also required for the treatment of diseases associated with the excess accumulation of xenobiotic and essential metals in specific organs e.g., excess iron, copper, zinc and aluminium in the brain, all of which have been implicated in neurodegenerative diseases [1,17]. Such strategies should include the selection of specific chelators that can cross the blood-brain barrier such as deferiprone [18,19]. Substantial improvements have been observed in different categories of patients with neurodegenerative diseases using deferiprone including pantothenate kinase-associated neurodegeneration (PKAN) and Friedreich's Ataxia [12,[20][21][22][23][24].…”
Section: Examples Of the Clinical Applications Of Chelator Metal Compmentioning
confidence: 99%
“…1). In addition to UVR‐induced iron‐mediated oxidative damage to key cellular constituents in skin, several studies have been published that support the role of iron accumulation and mitochondrial dysfunction in the development and progression of various neurodegenerative disorders, including Parkinson's and Alzheimer's disease (60, 61, 65, 66). Thomsen et al (59) showed recently that chronic inflammation in the substantia nigra ( in vivo rat model) is marked by a profound increase in intracellular iron levels.…”
Section: Combinational Interventionmentioning
confidence: 99%
“…In addition to providing further insight into the participation of iron in the molecular mechanisms underlying the initiation and progression of neurodegeneration, the researchers highlighted the potential iron‐scavenging role of microglia in reducing oxidative damage caused by iron‐mediated ROS formation. Maher and Kontoghiorghes (65) demonstrated, in rat pheochromocytoma (PC12) cells, that the iron‐chelating agent deferiprone and several derivatives of this compound confer neuroprotection. The reduction in neurodegeneration was mediated through the targeting of free iron, resulting in a decreased level of iron and inhibition of cell death.…”
Section: Combinational Interventionmentioning
confidence: 99%
“…Accordingly, a wide range of compounds have been proposed for PD therapy [70], including iron chelators [71]. For instance, deferiprone has been widely used for the treatment of systemic iron-related diseases and for neurological pathologies, including PD [72], due to its low molecular weight and ability to cross the blood-brain barrier. Different studies demonstrated deferiprone's ability to chelate not only iron but also copper, aluminum and zinc [73], reducing their free radical catalytic activity [74].…”
Section: Parkinson's Diseasementioning
confidence: 99%